Sombor Index of Zero-Divisor Graphs of Commutative Rings - Gürsoy, Arif; ÜLKER, ALPER; Kırcali Gürsoy, Necla (Ovidius Univ Press, 2022)
In this paper, we investigate the Sombor index of the zero-divisor graph of DOUBLE-STRUCK CAPITAL Z (n) which is denoted by Gamma(DOUBLE-STRUCK CAPITAL Z (n) ) for n is an element of {p(alpha), pq, p (2) q, pqr} where p, q and r are distinct prime numbers. Moreover, we introduce an algorithm which calculates the Sombor index of Gamma(DOUBLE-STRUCK CAPITAL Z (n) ). Finally, we give Sombor index of product of rings of integers modulo n.
Keywords: Topological Indices; Sombor Index; Zero-divisor Graph; Vertex Degree; Algorithm